Association between new anthropometric indices and osteoporosis in Chinese postmenopausal women- retrospective study based on hospitalized patients in China - Zhao, Xin; Sun, Jianbin; Xin, Sixu; Zhang, Xiaomei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to investigate the correlation between new anthropometric indicators and osteoporosis in postmenopausal women, evaluate whether these indicators can be used for the screening of osteoporosis in postmenopausal women, and provide evidence for the prevention of osteoporosis and fractures in these patients.MethodsThis study retrospectively analyzed 470 females hospitalized in the Department of Endocrinology of Peking University International Hospital between January 2017 and August 2022. According to the bone mineral density (BMD) results, the subjects were divided into two groups: the normal group and the osteoporosis group.Results(1) Compared with the normal group, the women in the OP group were older, the levels of BMD were lower, and the levels of 25(OH)D were lower, with all the differences being statistically significant (p<0.05). The body shape index (ABSI), Chinese visceral fat index (CVAI), abdominal volume index (AVI), and body roundness index (BRI) were significantly higher, and the body mass index (BMI) was significantly lower in the Osteoporosis (OP) group than in the normal group (all p<0.05). (2) CVAI was negatively correlated with hip BMD and lumbar spine BMD (r=-0.35, p<0.05; r=-0.20, p<0.05). BRI was negatively correlated with hip and lumbar spine BMD (r=-0.37, p<0.05; r=-0.20, p<0.05). (3) After adjusting age, blood pressure (BP), blood glucose, blood lipids, estimated Glomerular Filtration Rate (eGFR) and Ca levels, high levels of CVAI, AVI and BRI were independent risk factors for OP (OR=4.27, 95%CI 2.49, 7.33; OR=2.08, 95%CI 1.23, 3.51; OR=6.11, 95% CI 3.39, 11.01). (4) The model for predicting the risk of OP using anthropometric indicators showed that the AUCs ranked CVAI > BRI > ABSI > AVI = BMI > lipid accumulation index (LAP) > waist-to-hip ratio (WHR) > waist-to-height ratio (WHtR).ConclusionThis clinical study showed that new anthropometric indicators are associated with osteoporosis in postmenopausal women. It is necessary to pay attention to CVAI, BRI, AVI, and other anthropometric indicators in postmenopausal women, which are also of great significance for the prevention of osteoporosis.